Tenascin-C Deficiency Is Associated With Reduced Bacterial Outgrowth During Klebsiella pneumoniae-Evoked Pneumosepsis in Mice - Meijer, Mariska T.; de Vos, Alex F.; Scicluna, Brendon P.; Roelofs, Joris J.; Abou Fayçal, Chérine; Orend, Gertraud; Uhel, Fabrice; van der Poll, Tom (Frontiers in Immunology, 2021)
Tenascin C (TNC) is an extracellular matrix glycoprotein that recently emerged as an immunomodulator. TNC-deficient (TNC-/-) mice were reported to have a reduced inflammatory response upon systemic administration of lipopolysaccharide, the toxic component of gram-negative bacteria. Here, we investigated the role of TNC during gram-negative pneumonia derived sepsis. TNC+/+ and TNC-/- mice were infected with Klebsiella pneumoniae via the airways and sacrificed 24 and 42 hours thereafter for further analysis. Pulmonary TNC protein levels were elevated 42 hours after infection in TNC+/+ mice and remained undetectable in TNC-/- mice. TNC-/- mice showed modestly lower bacterial loads in lungs and blood, and a somewhat reduced local – but not systemic – inflammatory response. Moreover, TNC-/- and TNC+/+ mice did not differ with regard to neutrophil recruitment, lung pathology or plasma markers of distal organ injury. These results suggest that while TNC shapes the immune response during lipopolysaccharide-induced inflammation, this role may be superseded during pneumosepsis caused by a common gram-negative pathogen.